Second language teacher education : international perspectives - Tedick, Diane J. (Lawrence Erlbaum Associates, 2005)
By bringing together research, theory, and best practices from a variety of contexts (ESL/EFL, foreign language, bilingual and immersion education), this book contributes to building meaningful professional dialogue among second-language teacher educators.